Interakcije med zdravili pri bolnikih na Kirurškem oddelku Splošne bolnišnice Murska Sobota - Kovačič, Alenka (Zdravstveno varstvo, 2010)
Background: Drug-drug interactions represent an important segment of drug related problems. It is well-known that clinically significant drug-drug interactions occur in 7% of patients taking simultaneously six to ten medicines. The higher the number of co-prescribed drugs the greater the rate of clinically significant drug-drug interactions and the higher is the probability of ineffective treatment and toxic effects of drugs. Drug-drug interactions are classified into five groups according to their clinical importance as type A, type B, type C, type D and type X interactions.Objective: The primary purpose of the study was to analyse drug interactions of type C, D and X in patients receiving simultaneously eight or more drugs, and to identify patients and combinations of drugs with expressed clinically significant interactions. Methods: The study included 53 patients hospitalized at the Surgical Department of the Murska Sobota General Hospital during the period 2006 - 2009, who were taking eight or more drugs concurrently. A pharmacotherapeutic review was performed for each patient, andthe drug therapy was checked for possible drug-drug interactions using Lexi-Comp Online TM .The ATC classification was used to identify type C, type D and type X interactions. Results: The review of therapies identified 426 drug-drug interactions of type C, 44 interactions of type D and one interaction of type X. The patients were prescribed 157 different drugs from 11 different ATC groups. On the basis of history and pharmacotherapeutic review clinically significant drug-drug interactions were identified in 12 patients (22.6%). Conclusions: A pharmacotherapeutic review is a convenient method for identifying individual drug interactions and a useful tool for adapting or changing pharmacotherapy. In patients receiving eight or more drugs concurrently, a pharmacotherapeutic review performed by a clinical pharmacist is the ultimate method that should be introduced in all hospital departments to ensure safe and effective use of medicines.
Keywords: drug; farmakoterapija; interakcije; klinični pomen; zdravila